Gas Discharge Resistance and Medium Damage Degree as Hydrate Dissociation at Different Ambient Conditions - Chen, Xueping; Zhang, Peng; Wu, Qingbai; Zhang, Lianhai; Li, Shuaijun; Zhan, Jing; Wang, Yingmei (Frontiers in Energy Research, 2021)
For the investigation on some hydrate dissociation behaviors at different ambient conditions, methane hydrates formed inside porous media with different saturations were dissociated by depressurizations. Plots of instantaneous flow rate of gas as dissociation versus production pressure as well as deformation of experimental sample versus accumulative amount of released gas were drawn. These two lines slopes are respectively characterized as gas discharge resistance, and reciprocal of latter one as damage degree of experimental samples. The results show that these formed hydrates at higher ambient conditions, i.e., temperature and pressure, possess higher saturation, which is beneficial to discharge gas and to keep experimental samples undamaged. And the non-uniformity of dissociation processes at different layer positions induced by depressurization is inhibited significantly, especially while combining extra heating. Hydrate saturation dominates total volume loss of these samples under loadings. These conclusions can provide reference for the prediction in gas discharge capability and media damage degree as hydrate dissociation at different experimental and natural ambient conditions.